Circulating Tumor DNA Assays in Clinical Cancer Research. (20th June 2018) - Ossandon, Miguel R; Agrawal, Lokesh; Bernhard, Eric J; Conley, Barbara A; Dey, Sumana M; Divi, Rao L; Guan, Ping; Lively, Tracy G; McKee, Tawnya C; Sorg, Brian S; Tricoli, James V
Abstract: The importance of circulating free DNA (cfDNA) in cancer clinical research was recognized in 1994 when a mutated RAS gene fragment was detected in a patient's blood sample. Up to 1% of the total circulating DNA in patients with cancer is circulating tumor DNA (ctDNA) that originates from tumor cells. As ctDNA is rapidly cleared from the blood stream and can be obtained by minimally invasive methods, it can be used as a dynamic cancer biomarker for cancer early detection, diagnosis, and treatment monitoring. Despite the potential for clinical use, few ctDNA assays have been cleared or approved by the US Food and Drug Administration. As tools for clinical and translational research, current ctDNA assays face some challenges, and more research is needed to advance use of these assays. On September 29–30, 2016, the Division of Cancer Treatment and Diagnosis at the National Cancer Institute convened a workshop entitled "Circulating Tumor DNA Assays in Clinical Cancer Research" to garner input from industry experts, academia, and government research and regulatory agencies to understand and promote the translation of ctDNA assays to clinical research, with potential to advance to use in clinical practice. This Commentary presents the topics of the workshop covered in the presentations and points made in the discussions that followed: 1) background on ctDNA, 2) potential clinical utility of ctDNA assays, 3) assay technology, 4) assay clinical and analytical validation, and 5) industry perspectives. Additional relevant information that has come to light since the workshop has been included.